EL ANTIGUO HOSPITAL SAN JUAN DE DIOS. UNA VALORACIÓN HISTÓRICA PARA SU RECONOCIMIENTO COMO BIEN DE INTERÉS CULTURAL DE BUCARAMANGA (2014)
This article is a historical valuation of the building of the old Hospital San Juan de Dios de Bucaramanga. It seeks to contribute to the recognition of the building as an architectural heritage of the city, and its inclusion in the list of Cultural Interest. The findings made by historical research are presented, highlighting the importance of this building for history of Bucaramanga, considering it was the first, and for a long time, the only public health institution that served the residents of Bucaramanga.